Analysis of Ivacaftor drug approval for cystic fibrosis patients with gating mutations. - Nemirajaiah, S. (The Young Researcher)
Cystic fibrosis is an inherited monogenetic disorder that leads to chronic respiratory and lung infections. These infections result in decreased quality of life in patients. Quality of life (QOL) can be attributed to many disease characteristics such as hospitalization, organ transplant, depression, and bacterial infections. Ivacaftor is the drug approved to treat cystic fibrosis patients with G551D gating mutation. The goal of this paper was to demonstrate how an earlier approval of Ivacaftor for all gating mutations would have helped the QOL for the subset of cystic fibrosis patients with non-G551D gating mutation. After reviewing studies from reputed sources about Ivacaftor treatment effects on disease characteristics, a total of twenty studies were reviewed, and nine studies were selected to conduct a meta-analysis. In the meta-analysis, forest plots for QOL outcomes were generated. Meta-analysis showed that Ivacaftor improved the disease characteristics/ bacterial infections and quality of life in cystic fibrosis patients.